PENGARUH PARTISIPASI ANGGARAN, MOTIVASI KERJA DAN AKUNTANSI PERTANGGUNGJAWABAN TERHADAP KINERJA MANAJERIAL PADA BUMN DI KOTA BANDA ACEH - Rizky, Muhammad; Islahuddin, Islahuddin (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2023)
This study investigates the effects of budget participation, work motivation, and responsibility accounting on managerial performance both partially and simultaneously. The population of this study was top-level managers and middle-level managers at state-owned companies in Banda Aceh. A total of 39 respondents were selected as samples from 13 companies using a simple random sampling technique. This study uses primary data collected through questionnaires distributed to respondents to collect data. Statistical tests were performed using multiple linear regression analysis with the help of SPSS software. The results of the study prove that budget participation (X1), work motivation (X2), and responsibility accounting (X3) have a partial and simultaneous effect on managerial performance (Y).